Identification of the featured-element in fine road dust of cities with coal contamination by geochemical investigation and isotopic monitoring. (July 2021) - Liu, Yuan; Liu, Guijian; Yousaf, Balal; Zhou, Chuncai; Shen, Xiaofei
Highlights: Elements enriched in road dust include Zn, Hg, Pb, Cu, Cd, and Cr. Explored the pipeline of determining the featured-element of coal exploitation. XPS analysis of Hg spectra implied the impact of coal utilization on road dust. Hg had no health risk while Pb, Cr and As had risk not caused by coal utilization. Abstract: The exploitation of coal releases large amounts of contaminants into the environment. However, the featured pollutants of coal utilization as well as the scope and degree of their impact remain to be revealed. To identify the featured-element of coal contamination in a complex environment, a typical coal resource city was selected, and the major elements, 18 trace elements, as well as δ 13 C, δ 15 N, and δ 34 S in the fine road dust and certain source materials were analyzed. Through multiple analysis methods, the featured-element was determined step-by-step: firstly, elements with enrichment coefficients greater than two in road dust were focused: Zn, Hg, Pb, Cu, Cd, and Cr; secondly, difference analysis showed a significant difference (p < 0.05) of Hg and Cu concentration at different distance from the coal-fired power plant, making Hg and Cu the only candidates for the featured-element; finally, through coal-related source materials determination, Cu was not qualified as a featured-element. Therefore, Hg was the only left element to be considered as the featured-element. To be more convincing, more analyses were performed to support Hg as the featured-element: cluster analysis and isotope monitoring indicated Hg in road dust could originate from coal combustion; X-ray photoelectron spectroscopy was also conducted, where the forms of Hg in road dust with possible source materials were compared, and the presence of HgO and Hg only in the road dust near the power plant indicated the impact of the power plant on the surrounding dust. Through the health risk assessment, it was found that Hg in the road dust had no health risk, though the study area still had Pb, Cr, and As risks, which were not closely related to the pollutants released by coal-related sources.